1984
DOI: 10.1128/iai.43.3.1072-1079.1984
|View full text |Cite
|
Sign up to set email alerts
|

Local tissue temperature: a critical factor in the pathogenesis of bovid herpesvirus 2

Abstract: The effect of local tissue temperature on bovid herpesvirus 2 lesions in bovine skin was studied. Two areas of thoracic skin were multiply inoculated with virus and maintained at different temperatures; one above and the other below the rectal temperature of the animal. An entire inoculation site was removed daily from each area and subjected to virus, viral antigen, and interferon titrations and both light and electron microscopic examinations. Lesions in cold skin appeared sooner after inoculation, were larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Factors like UV radiation or marked temperature fluctuations might favor reactivation of latent infections and thus virus spread and/or the re-stimulation of antibody responses. The effect of skin temperature on BoHV-2 infections has been clearly shown previously, proposing an explanation for the seasonality of BHM-outbreaks [8,35].…”
Section: Discussionmentioning
confidence: 70%
“…Factors like UV radiation or marked temperature fluctuations might favor reactivation of latent infections and thus virus spread and/or the re-stimulation of antibody responses. The effect of skin temperature on BoHV-2 infections has been clearly shown previously, proposing an explanation for the seasonality of BHM-outbreaks [8,35].…”
Section: Discussionmentioning
confidence: 70%
“…The localized nature of cutaneous BoHV-2 replication and pathology has been previously attributed to the route of virus penetration/exposure, specific virus tropism and, additionally, to the surface temperature which may favor virus replication (Letchworth et al 1982a). In fact, early studies have demonstrated that BoHV-2 replicates more efficiently at lower temperatures (30-3 o C), comparing to replication at physiological bovine temperatures (38-39 o C) (Letchworth et al 1982a, Letchworth & Carmichael 1984. The preference for replication at low temperatures might also explain the higher incidence and distribution of BoHV-2 in regions of temperate climate (Letchworth & Carmichael 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, early studies have demonstrated that BoHV-2 replicates more efficiently at lower temperatures (30-3 o C), comparing to replication at physiological bovine temperatures (38-39 o C) (Letchworth et al 1982a, Letchworth & Carmichael 1984. The preference for replication at low temperatures might also explain the higher incidence and distribution of BoHV-2 in regions of temperate climate (Letchworth & Carmichael 1984). On the other hand, systemic viral spread has been demonstrated only after IV inoculation (Castrucci et al 1977(Castrucci et al , 1978.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal temperature for BHV-2 replication is lower than the normal body temperature. This might explain why the skin lesions are restricted to the teat and udder and the seasonality of the disease as well (8). The number of clinically affected animals during an outbreak is highly variable and depends on the animals' immune status.…”
Section: Discussionmentioning
confidence: 99%